1997
DOI: 10.2337/diacare.20.3.405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electrical Stimulation on Wound Healing in Patients With Diabetic Ulcers

Abstract: Electrical stimulation, given daily with a short pulsed, asymmetric biphasic waveform, was effective for enhancement of healing rates for patients with diabetes and open ulcers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
182
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(184 citation statements)
references
References 0 publications
2
182
0
Order By: Relevance
“…The clinical advantage of HVES is that the stimulation is confortable and affects sensory, motor and nociceptive nerve fibers. The physical parameters involved in this current allow for several therapeutic effects, such as pain and edema control 22 , as well as acceleration of tissue repair 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical advantage of HVES is that the stimulation is confortable and affects sensory, motor and nociceptive nerve fibers. The physical parameters involved in this current allow for several therapeutic effects, such as pain and edema control 22 , as well as acceleration of tissue repair 23,24 .…”
Section: Discussionmentioning
confidence: 99%
“…Phasic electrical stimulation is often employed, which favors nerve activation, and indeed improves nerve function in diabetic rat, 106,107 as well as increasing wound healing in diabetic mice 108 and man. 109 Less is known about the effects of prolonged DC stimulation at a level to mimic naturally occurring wound potentials, although in nondiabetic patients and animals there is usually an improvement in wound tensile strength. 54 An in-depth study of diabetic electrophysiology (TEP and wound currents in diabetic skin/cornea) would be beneficial.…”
Section: Diabetic Disease Modelmentioning
confidence: 99%
“…Thus, the size of the wound may not have provided sensitivity to demonstrate the actual changes. The macroscopic analysis to verify the effect of the TENS on wound healing has already demonstrated satisfactory results in diabetic wounds (6,15), leprosy wounds (16), pressure ulcers (17,18), burn injuries (10) and chronic venous ulcers (19 -21), which are wounds that have total areas greater than 8mm.…”
Section: Discussionmentioning
confidence: 99%
“…The existing scientific basis regarding the use of TENS in wound healing is more evident for chronic wounds initiated or aggravated by diseases such as diabetes (15), leprosy (16), peripheral arterial insufficiency (6,22), chronic venous insufficiency (19 -21) and in pressure ulcers in patients with spinal cord injuries (17,18). Considering acute wounds, animal studies have demonstrated that low-frequency TENS optimized the healing of burn lesions in elderly rats (10), improved healing by increasing growth factors in the dermis and epidermis (13) and reduced proinflammatory cytokines in the dermis by inhibiting the inflammatory phase, promoting a decrease in the duration of the cicatrization process (23).…”
Section: Introductionmentioning
confidence: 99%